The Use of Single Cell Mass Cytometry to Define the Molecular Mechanisms of Varicella-Zoster Virus Lymphotropism - Sen, Nandini; Mukherjee, Gourab; Arvin, Ann M. (Frontiers in Microbiology, 2020)
Unraveling the heterogeneity in biological systems provides the key to understanding of the fundamental dynamics that regulate host pathogen relationships at the single cell level. While most studies have determined virus-host cell interactions using cultured cells in bulk, recent advances in deep protein profiling from single cells enable the understanding of the dynamic response equilibrium of single cells even within the same cell types. Mass cytometry allows the simultaneous detection of multiple proteins in single cells which helps to evaluate alterations in multiple signaling networks that work in tandem in deciding the response of a cell to the presence of a pathogen or other stimulus. In applying this technique to studying varicella zoster virus (VZV), it was possible to better understand the molecular basis for lymphotropism of the virus and how virus-induced effects on T cells promoted skin tropism. While the ability of VZV to manifest itself in the skin is well established, how the virus is transported to the skin and cause the characteristic VZV skin lesions was not well elucidated. Through mass cytometry analysis of VZV-infected tonsil T cells we were able to observe that VZV unleashes a ‘remodeling’ program in the infected T cells that not only makes these T cells more skin tropic but also at the same time induces changes that make these T cells unlikely to respond to immune stimulation during the journey to the skin.